Twist1 Contributes to the Maintenance of Some Biological Properties of Dermal Papilla Cells in vitro by Forming a Complex With Tcf4 and β-Catenin - Yu, Nanlan; Hu, Tianxing; Yang, Haichao; Zhang, Lian; Song, Qin; Xiang, Fei; Yang, Xichuan; Li, Yuhong (Frontiers in Cell and Developmental Biology, 2020)
Objective: During hair follicle regeneration, hair follicle stem cells (HFSCs) are regulated by signals from dermal papilla cells (DPCs). Previously we found that Tcf4 could promote the proliferation of DPCs. In this study, we focused on whether and how the biological properties of Tcf4-induced DPCs were regulated by Twist1. Methods: Twist1 was overexpressed or knocked down in DPCs following different adenovirus or lentivirus infection. Phase-contrast microscopy was used to observe the agglutinative growth of DPCs. The CCK-8 assay was used to test the proliferation of DPCs. Western blot and qPCR experiments were used to determine the expression of HGF, IGF-1, VEGF, c-myc, survivin, and CyclinD1 in DPCs. ELISAs were used to test the growth factors secreted by DPCs. Conditional medium culture was used to detect the inductive ability of DPCs. Coimmunoprecipitation and immunofluorescence were used to test the binding of Twist1, Tcf4 and β-catenin in DPCs. Immunofluorescence was also used to test the expression of Twist1, Tcf4 and KRT15 in hair follicles. Results: Twist1 induced DPC agglutinative growth and proliferation. Twist1 upregulated the expression of downstream target genes downstream of Tcf4, c-myc, survivin, in Tcf4-induced DPCs, as well as the expression and secretion of growth factors HGF, IGF-1, VEGF, which had the ability to induce hair follicle growth. The conditional medium from Twist1-treated DPCs increased the expression of KRT40 and MSX2 in HaCaT cells. Twist1 and Tcf4 colocalized in DPCs both in vitro and in vivo. Anti-Twist1 precipitated Tcf4 and β-catenin. Conclusion: These results indicate that Tcf4 and Twist1 play a synergistic role in regulating the hair follicle induction ability of DPCs. Twist1 functions by forming a ternary complex with Tcf4 and β-catenin. Thus, we report new data that elucidate whether and how Twist1 regulates the biological properties of DPCs.